THE ROLE OF DHUAFA WALLETS IN THE DEVELOPMENT OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMEs) CASE STUDY OF THE FEBI CONTAINER CANTEEN, UINFAS BENGKULU - Lesti; Muhammad Ma’shum (Sekolah Tinggi Ilmu Ekonomi Syariah Nahdlatul Ulama Bengkulu, 2025)
This study aims to analyze the role of Dompet Dhuafa Bengkulu in supporting the development of Micro, Small, and Medium Enterprises (MSMEs) through the Container Canteen program at the Faculty of Economics and Islamic Business (FEBI), UIN Fatmawati Sukarno, Bengkulu. A qualitative descriptive method with a case study approach was used. Data collection techniques included in-depth interviews, participatory observation, and documentation. The study findings indicate that Dompet Dhuafa plays a role in providing initial capital, training, and managerial assistance to MSME actors at the canteen. In addition to its economic impact, which includes increased income for the surrounding community, the program also fosters a social impact by establishing an Islamic economic ecosystem within the campus. In conclusion, this Sharia-based MSME empowerment program by Dompet Dhuafa has significant potential to enhance sustainable economic and social welfare.